Capture and detection of cancer cells in whole blood with magnetic–optical nanoovals. (April 2014) - Bhana, Saheel; Chaffin, Elise; Wang, Yongmei; Mishra, Sanjay R; Huang, Xiaohua
Aim: To develop a simple assay for the capture and detection of rare cancer cells in whole blood using iron oxide–gold (IO–Au) nanoparticles.Materials & methods: IO–Au nanoovals (NOVs) were synthesized, coated with Raman tags and linked with antibodies targeting breast cancer. An integrated system was constructed for on-line magnetic cell capture and surface-enhanced Raman scattering (SERS) detection. The capabilities of IO–Au SERS NOVs to capture and detect rare cancer cells in blood were investigated in the integrated system using circulating tumor cell-mimic SK-BR-3 cells.Results: SK-BR-3 cells in whole blood were magnetically captured under a flow condition using IO–Au SERS NOVs, followed by on-line SERS detection with a limit of detection of 1–2 cells/ml blood.Conclusion: We developed a sensitive method that can capture and detect cancer cells in whole blood with a single nanoconstruct, which is highly promising for the detection of circulating tumor cells in the clinic. Original submitted 7 December 2012; Revised submitted 25 March 2013